A fadiga no exercício físico é modulada pela neurotransmissão colinérgica nos núcleos ventromediais hipotalâmicos, em ambiente frio - Juliana Bohnen Guimaraes (2007)
Cholinergic blockade in the ventromedial hypothalamic nucleus (VMH) reduces tailheat loss and induces a higher increase in the heat storage rate during physicalexercise, antecipating the onset of fatigue in 37%. Although the evidences indicatingthe involvement of VMH cholinergic receptors on thermoregulation during theexercise until fatigue, the control of these nucleus in an ambiental condition which theheat production is not different from the heat dissipation to the environment has notbeen described. In these conditions, the heat variation rate and the activation oftemperature sensitive neurons would not be altered in control group and, thus, thefatigue would be related to factors other than the thermoregulatory adjustments.Furthermore, it is unclear if the VMH thermogenic activity depends on ambienttemperature and exercise-induced increase in metabolic rate. Therefore, the aim ofthe study was to determine an ambient temperature where the internal bodytemperature is not altered during the physical exercise until fatigue and to verify theeffect of physical exercise and ambient temperature on thermogenic activity of VMH.Adult male Wistar rats weighting 250-350 g were used. The study was divided in twoexperimental protocols. During the first experimental protocol, intact rats weresubmited to treadmill running (20 m/min and 5% inclination) until fatigue at ambienttemperatures of 8ºC, 12ºC and 15ºC and with relative humidity controlled at 50%.Internal body temperature reduced during the exercise at 8ºC and increased at 15ºC.During the exposure to 12ºC, internal body temperature was not modificated from thebeginning of the exercise until the fatigue point. Tail skin temperature decreased twominutes after the exercise had started and remained reduced until the onset offatigue at the three ambient temperatures.During the second experimental protocol, animals were fixed to a stereotaxicapparatus and received a bilateral implant of cannulae in the VMH. The rats weresubmitted to two experimental conditions with an interval of at least two daysbetween the trials. Rats received an injection of either 0,2 µL of 0,15 M salinesolution or 2,5x10-2 M methylatropine in the VMH and, immediately after thisprocedure, the animals were submitted to exercise. Internal body temperature, tailskin temperature and time to fatigue were measured. This protocol was reproducedat different ambients temperatures of 5ºC, 12ºC and 15ºC and with relative humidityalways controlled at 50%. Cholinergic blockade in the VMH reduced the time tofatigue at the three ambients temperatures. Internal body temperature reducedduring the physical exercise at 5ºC increased under 15ºC and was not modified at12ºC. Methylatropine injection in the VMH failed to change internal body temperaturecompared to saline group. Tail skin temperature reduced during the exercise in bothgroups in all environmental conditions. No differences were observed in tail skintemperature between saline and methylatropine groups at the three ambienttemperatures.Taking the above data into account, we concluded that exercising running rats at12ºC represents an experimental protocol where the internal body temperature doesnot alter throughtout the exercise until the onset of fatigue. Furthermore, VMHmuscarinic cholinoceptors determine the time to fatigue regardless of the ambienttemperature in which the physical activity is carried out.